Pengaruh Intensitas Bermain Game Online Terhadap Prestasi Akademik Mahasiswa - Muhammad Mugni Firdaus; Jovan Athallah Putra Irawan; Sri Mulyeni (Journal of Creative Student Research, 2026)
Rapid developments in digital technology have contributed to major transformations in education, particularly regarding students’ learning behaviors. learning patterns. One of the impacts of this development One consequence of technological advancements is the rising frequency of online gaming among university students. Such games serve as readily available and favored entertainment options, yet overuse can interfere with students' focus on learning, effective time allocation, and overall academic achievements. This research seeks to investigate the effects of online gaming intensity on students' academic performance, drawing from prior studies. The methodology adopted is a literature review utilizing a qualitative descriptive approach. Data were gathered by examining diverse scholarly articles, both national and international journals, and pertinent literature that address online gaming intensity and its relation to academic outcomes in university settings. The findings reveal that elevated levels of online gaming typically exert adverse influences on academic performance, evidenced by diminished concentration during study, reduced academic motivation, impaired time management abilities, and increased instances of academic procrastination. Conversely, when engaged in at moderate and regulated levels, online games can offer beneficial effects as sources of recreation and stress alleviation. Ultimately, the influence of online gaming on academic success hinges on students' capacity to balance time, regulate gaming habits, and prioritize scholarly commitments.